Foresight As a Foundation to Understanding Trade-offs - CGIAR Independent Science for Development Council (CGIAR Independent Advisory and Evaluation Service, 2020)
The ISDC 2020 workplan focuses on CGIAR System Council’s request for thought-leadership to the System on trade-offs. Responsible science takes time. The research and analysis underpinning ISDC’s advice on trade-offs will fill key gaps in the agri-food literature which is necessary for CGIAR to make evidence-based decisions.